Diastereomers of Spheroidal Form and Commercially Available Taxifolin Samples - Roman P. Terekhov; Evgeny S. Melnikov; Ilya D. Nikitin; Margarita A. Tokareva; Tatyana A. Rodina; Anastasiya D. Savina; Denis I. Pankov; Anastasiya K. Zhevlakova; Vladimir L. Beloborodov; Irina A. Selivanova (MDPI AG, 2024)
Taxifolin is a natural polyphenol belonging to the class of flavonoids. The structure of this compound is characterized by the presence of two chiral centers. The spheroidal form of taxifolin (TAXs) has emerged as a promising modification due to enhanced solubility, higher safety profile, and long-term release from solid dosage forms. The study's objective was to assess the diastereomeric content in TAXs and industrially produced samples of taxifolin. Considering the difference in the physico-chemical properties of diastereomers and based on the literature data, we developed a qualitative HPLC method. The chromatograms were recorded using a diode array detector at 290 nm and a mass spectrometer operated in negative ionization mode. Our data suggest that a biphenyl column and gradient elution using 0.1% formic acid in water and 0.2% formic acid in methanol, with the organic phase gradient from 7% to 21% and a flow rate of 0.65 mL/min for 15 min at 60 °C, provides the best conditions for the separation of taxifolin diastereomers. This method was validated for quantitative analysis. We discovered that the cis-isomer was present in all the analyzed samples, with its quantity ranging from 0.8% to 9.5%. TAXs can be considered a sample enriched with diastereomers.